2006
DOI: 10.2478/s11658-006-0039-x
|View full text |Cite|
|
Sign up to set email alerts
|

A comparative gene-expression analysis of CD34+ hematopoietic stem and progenitor cells grown in static and stirred culture systems

Abstract: Static and stirred culture systems are widely used to expand hematopoietic cells, but differential culture performances are observed between these systems. We hypothesize that these differential culture outcomes are caused by the physiological responses of CD34 + hematopoietic stem and progenitor cells (HSPCs) to the different physical microenvironments created in these culture devices. To understand the genetic changes provoked by culture microenvironments, the gene expression profiling of CD34 + HSPCs grown … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 21 publications
(14 reference statements)
0
13
0
Order By: Relevance
“…The feasibility of cultivating different stem cells has been demonstrated for various types of bioreactors such as perfusion reactors, rotating vessels, spinner reactors, and others (Cameron et al, 2006;Fok and Zanstra, 2005;Gilbertson et al, 2006;Li et al, 2006;Liu et al, 2006;Zhao et al, 2005;Bauwens et al, 2005;Schroeder et al, 2005). Ideally, a bioreactor should provide a homogeneous environment, for a high concentration of cells, and allow easy access for sampling.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The feasibility of cultivating different stem cells has been demonstrated for various types of bioreactors such as perfusion reactors, rotating vessels, spinner reactors, and others (Cameron et al, 2006;Fok and Zanstra, 2005;Gilbertson et al, 2006;Li et al, 2006;Liu et al, 2006;Zhao et al, 2005;Bauwens et al, 2005;Schroeder et al, 2005). Ideally, a bioreactor should provide a homogeneous environment, for a high concentration of cells, and allow easy access for sampling.…”
Section: Discussionmentioning
confidence: 99%
“…Employing a scalable reactor system can enable a sufficient supply of differentiation competent or differentiated cells to meet such a clinical need. Since the conventional method of expanding and differentiating stem cells in tissue culture plates is labor intensive and difficult to scale up, different culture systems for expansion and differentiation of stem cells have been investigated; rotary culture systems, perfusion culture systems, and stirred suspension systems have been employed for various stem cell cultures (Cameron et al, 2006;Fok and Zanstra, 2005;Gilbertson et al, 2006;Li et al, 2006;Liu et al, 2006;Zhao et al, 2005;Bauwens et al, 2005;Schroeder et al, 2005). Among those systems, stirred suspension culture has the advantage of having been widely used in growing mammalian cells for decades.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hematopoietic stem and progenitor cells (HSPCs) were among the first stem cells to be cultured in bioreactors. Two recent studies have confirmed that HSPC expansion is more extensive in stirred or suspended culture [2,3]. In contrast to HSPCs, most bioreactor studies with mesenchymal stem cells (MSCs) have employed perfusion of cells embedded within a 3-dimensional (3-D) scaffold.…”
Section: Stem Cell Expansion and Differentiation In Bioreactorsmentioning
confidence: 99%
“…The magnetic separation step was repeated to further purify CD34 + cells. The purity of isolated CD34 + cell population is stated as > 95% [14].…”
Section: `éääëmentioning
confidence: 99%